Exit Polls and Voter Turnout - Asger Lau Andersen; Thomas Jensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2010)
We set up a model of elections or referendums with two alternatives to study how voter turnout and election outcomes are affected by the publication of exit polls on election day. We find that the introduction of an exit poll influences the incentive to vote both before and after the poll is published, but the signs of the effects are generally ambiguous. The fact that exit polls influence the incentive to vote before they are even published is sometimes overlooked in the debate on their desirability. We show that this can lead to premature conclusions about the impact of exit polls on election outcomes.
Keywords: D71; D72; D82; 330; elections; exit polls; voter turnout; Wahlverhalten; Asymmetrische Information; Neue politische Ökonomie; Theorie